Pre-Groove Development for Laser Cleaving of Brittle Materials by Using Micro-Lens - Takanori ISHIKAWA; Takashi UEDA; Tatsuaki FURUMOTO; Akira HOSOKAWA; Ryutaro TANAKA (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2012)
Thermal stress cleaving is a prospective technique for separating thin plates of brittle materials such as silicon, ceramic and glass. This study, deals with a new method which provide the initial fracture on the edge of workpiece. The initial fracture such as crack, scratch and groove is the starting point of crack propagation in laser cleaving and the crack propagates along laser scanning path from the initial fracture. In previous study, the initial fracture is created by Vickers indenter. Since shape of Vickers indenter is pyramid, the unnecessary cracks propagate. In addition, lateral cracks are created at the surface. Because of cracks, the quality of thermal stress cleaving is poor. In this study, a pre-groove is used as the initial fracture. The pre-groove is formed on the workpiece surface by pulsed Nd:YAG laser irradiation through a cylindrical micro-lens. The cylindrical micro-lens is made by the irradiation of Er:YAG laser to the surface of acrylic board. Silicon wafer is used as a workpiece. Continuous Nd:YAG laser is used for laser cleaving. By using this method, there is no unnecessary cracks happen, and subsequently improve the quality of thermal stress cleaving.